2018
DOI: 10.1177/1756284818775054
|View full text |Cite
|
Sign up to set email alerts
|

Not only stem cells, but also mature cells, particularly neuroendocrine cells, may develop into tumours: time for a paradigm shift

Abstract: Stem cells are considered the origin of neoplasms in general, and malignant tumours in particular, and the stage at which the stem cells stop their differentiation determines the degree of malignancy. However, there is increasing evidence supporting an alternative paradigm. Tumours may develop by dedifferentiation from mature cells able to proliferate. Studies of gastric carcinogenesis demonstrate that mature neuroendocrine (NE) cells upon long-term overstimulation may develop through stages of hyperplasia, dy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 160 publications
0
10
0
Order By: Relevance
“…Gastric carcinoids are members of a family of principally gastro-entero-pancreatic (GEP) neuroendocrine tumors (NETs), although related similar tumors also occur in other organs. The incidence of gastric carcinoids has increased up to 15-fold over the past 3 decades, a period characterized by a parallel major increase in the use of acid-secretory-suppressing proton pump Furthermore, studies suggest that not only stem cells but also mature neuroendocrine cells, upon long-term over stimulation by gastrin, may progress through hyperplasia and dysplasia into highly malignant carcinomas [49]. Together, these observations suggest that by causing hypergastrinemia, widespread use of PPIs, often for many years and particularly in patients with intractable reflux disease, may be contributing to increase in the occurrence of many cancers, both within and outside the gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gastric carcinoids are members of a family of principally gastro-entero-pancreatic (GEP) neuroendocrine tumors (NETs), although related similar tumors also occur in other organs. The incidence of gastric carcinoids has increased up to 15-fold over the past 3 decades, a period characterized by a parallel major increase in the use of acid-secretory-suppressing proton pump Furthermore, studies suggest that not only stem cells but also mature neuroendocrine cells, upon long-term over stimulation by gastrin, may progress through hyperplasia and dysplasia into highly malignant carcinomas [49]. Together, these observations suggest that by causing hypergastrinemia, widespread use of PPIs, often for many years and particularly in patients with intractable reflux disease, may be contributing to increase in the occurrence of many cancers, both within and outside the gastrointestinal tract.…”
Section: Resultsmentioning
confidence: 99%
“…While gastric carcinoids, despite their marked increase, occur much less frequently than carcinoids in the lung, rectum, small intestine, and pancreas, these other tumors also display marked increases in their occurrence over the same time period (Figure 2), although serum gastrin has not been studied in affected patients [4,11]. Furthermore, studies suggest that not only stem cells but also mature neuroendocrine cells, upon long-term over stimulation by gastrin, may progress through hyperplasia and dysplasia into highly malignant carcinomas [49].Together, these observations suggest that by causing hypergastrinemia, widespread use of PPIs, often for many years and particularly in patients with intractable reflux disease, may be contributing to increase in the occurrence of many cancers, both within and outside the gastrointestinal tract. The true extent of possible extra-intestinal stimulation has not been studied, but examination of elevations of serum chromogranin A has been associated with the presence of tumors of pituitary, parathyroid, thyroid, medullary thyroid, adrenal, lung small cell, prostate, and neural (Schwannoma) origin [34], suggesting that growth in these also may possibly be stimulated by hypergastrinemia.…”
Section: Evidence Of Causationmentioning
confidence: 99%
“…An alternative paradigm to the stem cell theory as the tumour cell of origin has been gaining ground in recent years. In certain circumstances mature neuroendocrine cells may dedifferentiate, accumulate mutations and other genomic events and become tumour cells themselves[102]. Neuroendocrine tumours are the most likely results of such an event but also gastric adenocarcinomas.…”
Section: The Correa Cascade and Diffuse Gcmentioning
confidence: 99%
“…Primary hepatic NETs are thought to originate from NET cells that may subsequently propagate to the intrahepatic biliary tree and become cancerous [ 6 ]. Additionally, some investigators have suggested that transdifferentiation of cancerous stem cells into NET cells may cause the cells to undergo neuroendocrine differentiation [ 7 ]. The World Health Organization classifies NETs of the liver into three grades: type I or well-differentiated tumors, which have a good prognosis; type II or moderately differentiated tumors; and type III or poorly differentiated tumors, which carry a poor prognosis.…”
Section: Discussionmentioning
confidence: 99%